2017
DOI: 10.4103/jcis.jcis_65_17
|View full text |Cite
|
Sign up to set email alerts
|

Breast Involvement by Hematologic Malignancies: Ultrasound and Elastography Findings with Clinical Outcomes

Abstract: Objective:Hematological malignancies very rarely involve the breast. The aim of this study is to retrospectively evaluate B-mode ultrasound (US) and elastography (ES) findings of breast involvement by hematologic malignancies with clinical outcomes.Materials and Methods:All core-needle biopsy results that were performed at our tertiary breast center from January 2013 to September 2016 were searched. Our search revealed 9 patients with breast involvement either by leukemia or lymphoma. All patients were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
14
1
Order By: Relevance
“…The elastography findings of intramammary hematologic malignancy have rarely been reported on [3842]. Aslan et al conducted a study in which they assessed the elasticity of intramammary hematologic malignancies in 9 patients; the study revealed that the elasticities of intramammary hematologic malignancy are variablesoft in 2 patients, intermediate in 5, and high in 2 [39]. Of the 9 hematologic malignancy cases, only 1 was myeloid sarcoma, which demonstrated intermediate elasticity (shear-wave velocity: 4.68 to 5.74 m/s, virtual touch imaging: diffuse dark, same size with B-mode ultrasonography) [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elastography findings of intramammary hematologic malignancy have rarely been reported on [3842]. Aslan et al conducted a study in which they assessed the elasticity of intramammary hematologic malignancies in 9 patients; the study revealed that the elasticities of intramammary hematologic malignancy are variablesoft in 2 patients, intermediate in 5, and high in 2 [39]. Of the 9 hematologic malignancy cases, only 1 was myeloid sarcoma, which demonstrated intermediate elasticity (shear-wave velocity: 4.68 to 5.74 m/s, virtual touch imaging: diffuse dark, same size with B-mode ultrasonography) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 9 hematologic malignancy cases, only 1 was myeloid sarcoma, which demonstrated intermediate elasticity (shear-wave velocity: 4.68 to 5.74 m/s, virtual touch imaging: diffuse dark, same size with B-mode ultrasonography) [39]. The published cutoff shear-wave velocity value for malignancies ranges from 4.1 to 5.2 m/s [39]. Another report also described the elastography findings of myeloid sarcoma of the breast, in which the Tsukuba elasticity score, strain index, and elasticity ratio were 2, 2.3, and 0.71, respectively; these values indicated a benign nature [38].…”
Section: Discussionmentioning
confidence: 99%
“…MRI may show non-mass enhancement, solitary or multiple enhancing masses 4. MRI may show T2 hyperintensity signal or ring enhancement due to underlying peripheral angiogenesis and central necrosis 5.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the diagnosis would be more challenging if breast leukaemia infiltration is the only presentation 4. In the setting of undetermined and non-specific breast imaging, breast core biopsy should always be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The central nervous system and testes are frequent locations and sanctuary sites for extramedullary relapses. Involvement of the breast by leukemia is uncommon but may manifest as an oncological emergency requiring prompt management[2-4]. Acute myeloid leukemia constitutes the most common type of acute leukemia in adults, and is also the most common type infiltrating the breasts.…”
Section: Introductionmentioning
confidence: 99%